The Significance of Financial Literacy for MSMEs - Siswati, Ari; Agung Wibowo, Mufti; Fauzi, Irsal; Ramadaey Bangsa, Jaya; Indah Isnawati, Setya; Aziz, Abdul (Yayasan Meira Visi Persada, 2024)
The purpose of this study is to emphasize the significance of financial literacy for MSMEs. This research utilizes a descriptive method with a qualitative approach. The primary and secondary data sources, along with data collection techniques such as observation, interviews, and documentation, are employed in this study. The instruments used in the research methodology include the researchers themselves, interview guidelines, and field notes. Financial literacy significantly impacts the sustainability and prosperity of micro, small, and medium enterprises (MSMEs). A thorough comprehension of financial principles enables MSME entrepreneurs to efficiently manage their resources, make informed decisions, and strategize for long-term growth. Financial literacy encompasses not only budget management and cash flow but also the capacity to plan investments, mitigate risks, and astutely seize economic opportunities. Proficiency in these skills empowers MSMEs to adapt to market dynamics, overcome challenges, and thereby support the sustainable expansion of their businesses in the long run.